Subbasin Characteristics and Hydrological Response to Anticipated Urbanisation - (:unkn) unknown (My University, 2008)
This study investigated the relationship between the hydrological response of a river basin to anticipated urbanisation and its subbasin characteristics by applying a hydrological model (HSPF) with land use scenarios generated by an urban growth model (LEAM). The hydrological model was set up and run for the Kishwaukee River basin in northeastern Illinois, USA. The results show that the subbasin size and imperviousness were found to be more correlated to runoff changes than slope. However, no basin characteristics have significant relationships with percent changes in any hydrological variables due largely to the effects of upstream subbasins. When the effects of upstream subbasins are excluded, it becomes clear that the subbasin size is negatively correlated with percent changes in total runoff, storm flow and peak flow. The percent change in impervious land is positively related to the percent changes in storm flow and peak flow, but the relationship itself is dependent on the initial imperviousness level. The geographical pattern of the basin response implies that it requires more targeted measures to mitigate negative hydrological impacts.
Keywords: hydrological model; urbanisation; HSPF; LEAM; runoff